2020
DOI: 10.1002/tal.1797
|View full text |Cite
|
Sign up to set email alerts
|

Seismic performance assessment of steel frames with shape‐memory alloy wire‐based dampers

Abstract: Steel braces reduce the interstory drifts of steel structures under earthquake excitations; however, severe earthquakes could still cause some notable residual drifts in the structures. The reduction of these residual drifts decreases post-earthquake retrofitting costs. This study investigates the seismic performance of steel frames

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Similar behavior of SMA is examined by reinforcing NiTi wires in a steel braced frame [11]. SMA wires-based dampers has been studied for vulnerability reduction in the braced frames [12]. Except SMA wires and bars, SMA rings are also utilized as damper device and the symmetry of single and dual rings have been also studied [13].…”
Section: Introductionmentioning
confidence: 99%
“…Similar behavior of SMA is examined by reinforcing NiTi wires in a steel braced frame [11]. SMA wires-based dampers has been studied for vulnerability reduction in the braced frames [12]. Except SMA wires and bars, SMA rings are also utilized as damper device and the symmetry of single and dual rings have been also studied [13].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the hysteresis diagram is stable and has good ductility and energy dissipation. Falahian et al [18] investigated the seismic performance of a steel frame equipped with a selfcentering damper. The results showed that the proposed damper limits the residual drifts.…”
Section: Introductionmentioning
confidence: 99%